Effect of Postharvest Ripening on the Phytochemical Composition and Antioxidant Properties of Fruits from Ten Plum (Prunus domestica L.) Cultivars - Monika Mieszczakowska-Frąc; Niall John Dickinson; Dorota Konopacka (Agronomy)
The purpose of this study was to determine the effect of postharvest ripening on the concentration of phenolic compounds and antioxidant activity in fruits of ten plum cultivars. The degree of ripeness was defined as the CIRG index, based on the CIE Lab color values and ranging from 1.05 to 10.04, soluble solids (12.9 to 20.7%), and firmness (4.47 to 13.64 N). Fruits were analyzed directly after harvest and after 3 and 6 days of storage at 18 °C. The CIRG index increased by 2% to 23% after 3 days of storage, and by as much as 64% after 6 days, depending on the cultivar. Ripening resulted in increased concentration of phenolic compounds and in higher antioxidant activity. The predominant compounds in the majority of the cultivars were proanthocyanidins, which constituted over 50% of the total polyphenols, at concentrations between 30 and 453 mg 100 g−1 FW. Additionally, postharvest ripening caused the proanthocyanidins to increase up to 76%. The polymerization of proanthocyanidins ranged from 6.6 to 20.0. For some cultivars, the concentration of anthocyanins approximately doubled after 6 days of fruit storage. Fruits of ‘Čačanska Najbolja’ and ‘Čačanska Lepotica’ were characterized by the highest concentration of bioactive compounds and the highest antioxidant activity.